2022
DOI: 10.1159/000522523
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Stool Microbiome in Newborns Undergoing Mild Therapeutic Hypothermia after Hypoxic-Ischemic Encephalopathy

Abstract: Background: Hypoxic-ischemic encephalopathy (HIE) is associated with brain injury in newborns, and may lead to disability or death. Mild therapeutic hypothermia (TH) is an effective neuroprotective intervention and an established standard of care in western countries. The gut microbiome, the genomic and physico-chemical contribution of the gut microbiota, serves important functions and is increasingly recognised as a major influencer on development. The impact of HIE and TH on the evolving gut microbiota of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Perinatal hypoxia-ischemia may cause gut barrier dysfunction, such as necrotizing enterocolitis ( Young et al, 2011 ). HIE has also been reported to alter the gut microbiota ( Ni et al, 2019 ; Gala et al, 2022 ). We found a decreased Firmicutes/Bacteroidetes ratio in HIDB rats, which indicated a dysbiosis in the gut microbiota ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perinatal hypoxia-ischemia may cause gut barrier dysfunction, such as necrotizing enterocolitis ( Young et al, 2011 ). HIE has also been reported to alter the gut microbiota ( Ni et al, 2019 ; Gala et al, 2022 ). We found a decreased Firmicutes/Bacteroidetes ratio in HIDB rats, which indicated a dysbiosis in the gut microbiota ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota is a part of the gut–brain axis, and the establishment and functional maturation of the key microbiome is crucial in early life ( Gala et al, 2022 ). Studies have shown that the microbiome plays an important, region-specific role in brain development as early as hours after birth ( Castillo-Ruiz et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing data was further processed for compositional analysis of microbial community using vegan package in R and statistical methods described elsewhere [ 44 , 45 ]. Briefly, Shannon index was calculated for measuring alpha-diversity for each sample (using the diversity function from vegan package in R).…”
Section: Methodsmentioning
confidence: 99%